New Readings and Interpretations on the Inscribed Stele from Ḥənzat (HS1) - Bulakh, Maria; Yohannes Gebre Selassie (Aethiopica, 2022)
In 1974 the renowned Ethiopianist Lanfranco Ricci inspected the site of Ḥǝnzat in central Tǝgray. Inter alia, he inspected and photographed a stele with a lengthy inscription. In 2014, Yohannes Gebre Selassie published an article on an inscription which he labelled HS1, and which he believed to be a second inscription on a stele found in Ḥǝnzat. However, close inspection reveals that HS1 is the same stele which Ricci saw and described. The contribution here presents evidence to support this claim. In addition, some new interpretations are offered as alternatives to Yohannes Gebre Selassie’s first translation.